Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/ol401478j
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic α,β-Tetrapeptoids: Sequence-Dependent Cyclization and Conformational Preference

Abstract: The presence of at least one N-Cα branched side chain is crucial for successful cyclization of α,β-tetrapeptoids. The ctct amide sequence revealed in the crystal structure of the 14-membered cyclotetrapeptoid 8 is also the most populated conformation in solution and is reminiscent of the predominant amide arrangement of the 12-membered cyclic tetrapeptides (CTPs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…An analysis of the ϕ and ψ angles present in published peptoid structures (41 crystal structures, 5 NMR structures, 132 total dihedral combinations, Supporting Information Table S1) reveal that trans‐ and cis ‐amides show similar preferences for ϕ and ψ combinations, with trans ‐amide and cis ‐amide residues primarily occupying two main regions that span across the bottom and top edges of the Ramachandran plot (ϕ 70° and −70° and ψ 180° and −180°, Figure ). Replotting these data to represent ϕ and ψ from 0° to 360° (adding 360° to ϕ and ψ values below 0°, Figure C,F) shows that the preferred dihedrals lay in the same low‐energy regions for trans and cis disarcosine calculatations, with regions centered around (70°, 180°) and (290°,180°) (Figure C,F).…”
Section: The Ramachandran Plotmentioning
confidence: 99%
“…An analysis of the ϕ and ψ angles present in published peptoid structures (41 crystal structures, 5 NMR structures, 132 total dihedral combinations, Supporting Information Table S1) reveal that trans‐ and cis ‐amides show similar preferences for ϕ and ψ combinations, with trans ‐amide and cis ‐amide residues primarily occupying two main regions that span across the bottom and top edges of the Ramachandran plot (ϕ 70° and −70° and ψ 180° and −180°, Figure ). Replotting these data to represent ϕ and ψ from 0° to 360° (adding 360° to ϕ and ψ values below 0°, Figure C,F) shows that the preferred dihedrals lay in the same low‐energy regions for trans and cis disarcosine calculatations, with regions centered around (70°, 180°) and (290°,180°) (Figure C,F).…”
Section: The Ramachandran Plotmentioning
confidence: 99%
“…19 We accomplished a comparable 71% yield of 6, a 15-atom cyclopenta-α-peptoid (entry 13). Swapping out the HOBt coreagent for the 7-aza analogue, 1-hydroxy-7-azabenzotriazole (HOAt), 20 we attained an astonishing increase in isolated yield to 97% of 6, with 90% for 4 but a disappointing 38% for 5 (entries 3, 6, and 15).…”
mentioning
confidence: 99%
“…The crystal structure showed that the peptoid adopted a β cis ‐α trans ‐β cis ‐α‐ trans configuration (Figure 4). 37 …”
Section: Head‐to‐tail Cyclisationmentioning
confidence: 99%